Analyzing Pension Data Process and Proposing Solutions at the Regional Financial and Asset Management Agency Office - Marlindawati, .; Syavira Dyah, Harumi (INTI International University, 2023)
The Regional Financial and Asset Management Agency (BPKAD), where we conducted our investigation, is one of the organizations under the mayor's jurisdiction in Palembang. Due to its manual management of employee pension data using Microsoft Excel, this organization has considerable influence over the Palembang municipal government, especially in pension data gathering. Began by contacting employees when their designated retirement date was drawing near. The employee then finishes the dossier, which becomes a pension proposal. The fact that the management is still done using the Excel program presents several difficulties. For instance, when the head of finance requires pension data, the staff of the department must review each retiring employee file in the Microsoft Excel application individually, in addition to having to review multiple other files. Naturally, it takes a while because the necessary data must be manually searched individually. When the file is complete, it will be submitted to the department for approval. In this regard, we offer a solution by creating and deploying an application to streamline the pension administration procedure.